Implementasi Structure Learning Approach (SLA) dalam Bimbingan Klasikal untuk Meningkatkan Karakter P5 Pada Siswa SMA - Nur Fadhilah Umar; Zulfikri; Asri Nur Aina; Muhammad Ansarullah S. Tabbu; Ahmad Fudhail Majid (IKRA-ITH ABDIMAS, 2025)
The implementation of the Pancasila Student Profile Strengthening Project (P5) requires pedagogical strategies and guidance services capable of developing students’ character in a systematic and contextually grounded manner. However, students at SMAN 23 Makassar demonstrate complex developmental dynamics, ranging from academic demands and involvement in school organizations to varying abilities in managing their roles within project-based learning. These conditions necessitate a more structured support approach to help students consistently internalize P5 values. This community engagement program applies the Structured Learning Approach (SLA) within classroom guidance services as a strategic intervention to enhance student character in alignment with the Pancasila Student Profile. The implementation method comprises five stages: needs identification, development of guidance materials, integration of P5 values into SLA sessions, implementation of classroom guidance, and evaluation and follow-up. The procedural activities include modeling, role-playing, group discussions, feedback provision, and transfer of training to ensure that students can effectively practice social–emotional skills within the context of P5 projects. The results indicate improvements in students’ assertive communication, collaboration skills, decision-making abilities, and awareness of the values of cooperation, independence, and critical thinking. The school counselor also reported that SLA offers a more systematic and applicable service framework for counseling practice. Overall, this program demonstrates that integrating SLA into classroom guidance effectively strengthens student character and supports the successful implementation of P5 projects at SMAN 23 Makassar. This service model holds potential for sustainable adoption as part of the school’s long-term character development initiatives.